IMPLEMENTASI NILAI KEARIFAN LOKAL DALAM PEMBELAJARAN DI SDN 15 INDRALAYA SEBAGAI UPAYA PENANAMAN PENDIDIKAN KARAKTER DI TENGAH ARUS GLOBALISASI - Khasanah, Uswatun (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
One of the problems that needs attention in the current era of globalization is the problem of Nationalism. The purpose of writing this article is that teachers who teach in schools can implement or implement elements of local wisdom in Ogan Ilir such as songket weaving craft, syarofal'anam, dul muluk, pindang Centella, in learning at school, so that arise in the students learn solid nationalism against their homeland to face the swift currents of globalization feared will impact on the erosion of a sense of love for local culture. This research uses qualitative descriptive method, research done in SDN 15 Indralaya involving teachers and students as the object of research. Data were collected through observation, interviews, and documentation obtained through photography. The results showed that students at SDN 15 Indralaya were willing to appreciate local wisdom in their area, and they were keen to learn and practice local art in daily life. By implementing the value of local wisdom in learning expected soul and spirit of student nationalism will remain firmly maintained in the midst of the swift current of globalization.